Risk Aversion in a Dynamic Asset Allocation Experiment. (October 2019) - Brocas, Isabelle; Carrillo, Juan D.; Giga, Aleksandar; Zapatero, Fernando
Abstract : We conduct a controlled laboratory experiment in the spirit of Merton (1971 ), in which subjects dynamically choose their portfolio allocation between a risk-free and risky asset. Using the optimal allocation of an investor with hyperbolic absolute risk aversion (HARA) utility, we fit the experimental choices to characterize the risk profile of our participants. Despite substantial heterogeneity, decreasing absolute risk aversion and increasing relative risk aversion are the predominant types. We also find some evidence of increased risk taking after a gain. Finally, the session level risk attitudes show a different profile than the individual descriptions of risk attitudes.